Antibiotics inhibit sphere-forming ability in suspension culture. Issue 1 (December 2016) - Relier, Sébastien; Yazdani, Laura; Ayad, Oualid; Choquet, Armelle; Bourgaux, Jean-François; Prudhomme, Michel; Pannequin, Julie; Macari, Françoise; David, Alexandre
Abstract Background This last decade, a lot of emphasis has been placed on developing new cancer cell culture models, closer to in vivo condition, in order to test new drugs and therapies. In the case of colorectal cancer, the use of patient biopsies to seed 3D primary cultures and mimic tumor initiation necessitates the use of antibiotics to prevent microbial intestinal contamination. However, not only long term use of antibiotics may mask the presence of low levels of microbial contamination, it may also impact cancer cell phenotype. Methods In this study we tested the impact of penicillin-streptomycin cocktail addition in both monolayer and suspension culture. To ensure the reliability of our observations we used six different cell lines and each experiment was performed in triplicate. Results were analyzed with Student's t test. Results We show that penicillin–streptomycin cocktail inhibits the sphere-forming ability of six cancer cell lines in suspension culture though it has no impact in monolayer culture. We correlate this effect with a significant decrease of cancer stem cells pool which holds self-renewal potential. Conclusions Overall, this study warns against systematic addition of antibiotics in growth medium and raises the interesting possibility of using antibiotics to target cancer stem cells.